A Reading in Arabic Language Problems according to Aishah Abdul Rahman (bint Syathi') | قراءة في إشكالية اللغة العربية عند عائشة عبد الرحمن بنت الشاطئ - Ahmadi Usman Sirathan (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2011)
The article deals with the Arabic language and its problem faced in the modernera. The article is a response for the invitation that invites to give attention forArabic Language because of danger threatened, and that danger will damageArabic character, tearing spirit, and affecting weakness agin westernization.This article is a study on the writing of Aisyah Abdurrahman (Bint asy-Syathi’)who has been recognized as one who has view and excellent thinking onlinguistic and modern literature, and who has fanaticism to the Arabian and itslanguage. The article mentions her important views in this area, among themare: al Fusha and al ‘Amiyah, Arabic language and modern knowledge, languageinvasion and Arabization battle, teaching Arabic language. The article refers tothe book “Lugatuna wa al Hayah” written by Bint asy-Syathi’, and also refers tomodern books that has correlation to the topic.